2015
DOI: 10.1016/j.healun.2014.11.007
|View full text |Cite
|
Sign up to set email alerts
|

Restrictive chronic lung allograft dysfunction: Where are we now?

Abstract: Chronic lung allograft dysfunction (CLAD) remains a frequent and troublesome complication after lung transplantation. Apart from bronchiolitis obliterans syndrome (BOS), a restrictive phenotype of CLAD (rCLAD) has recently been recognized, which occurs in approximately 30% of CLAD patients. The main characteristics of rCLAD include a restrictive pulmonary function pattern with a persistent decline in lung function (FEV1, FVC and TLC), persistent parenchymal infiltrates and (sub)pleural thickening on chest CT s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
60
0
2

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 75 publications
(66 citation statements)
references
References 31 publications
4
60
0
2
Order By: Relevance
“…Across studies analyzing the influence of CMV on the incidence of CLAD, the universal use of prolonged antiviral prophylaxis has been consistently associated with lower risk of BOS (55,56). Although the majority of studies have used BOS as the clinical end point, studies performed in the current era have not identified CMV as a potential cause of RAS (57).…”
Section: Type Of Organ Transplantmentioning
confidence: 99%
“…Across studies analyzing the influence of CMV on the incidence of CLAD, the universal use of prolonged antiviral prophylaxis has been consistently associated with lower risk of BOS (55,56). Although the majority of studies have used BOS as the clinical end point, studies performed in the current era have not identified CMV as a potential cause of RAS (57).…”
Section: Type Of Organ Transplantmentioning
confidence: 99%
“…Roughly speaking, approximately 70% of post-transplant patients affected by CLAD have BOS and 30% have the RAS clinical phenotype of CLAD [2,3,5,6]. Compared with the much better known BOS clinical phenotype, patients with RAS experience a worse prognosis (3.5 versus 1.5 years); the reasons for this difference in prognosis are poorly understood [7]. Patients affected by RAS appear to progress in a more stepwise pattern [8], that might be driven by intermittent up-regulation of pro-inflammatory mediators [9,10] during episodes of diffuse alveolar damage [11,12] similar to those observed in patients with idiopathic pulmonary fibrosis (IPF).…”
Section: Introductionmentioning
confidence: 99%
“…In single-lung transplanted recipients, accurate rCLAD diagnosis is more complicated, given the confounding effect of the native lung, but a FVC decrease >20% was also associated with a poor outcome in a multi-center cohort study (49). This poor outcome is also a common denominator in all aforementioned studies: independent of the criteria used to diagnose restriction, outcome was worse in patients with a restrictive (rCLAD) vs. an obstructive (BOS) pulmonary function defect, with a median post-diagnosis survival of 6-18 months in rCLAD compared to 3-5 years in BOS (50). Prevalence of rCLAD is quite similar across different centers with 25-35% of CLAD patients affected (50).…”
Section: Diagnosis Radiology and Pathologymentioning
confidence: 93%
“…This poor outcome is also a common denominator in all aforementioned studies: independent of the criteria used to diagnose restriction, outcome was worse in patients with a restrictive (rCLAD) vs. an obstructive (BOS) pulmonary function defect, with a median post-diagnosis survival of 6-18 months in rCLAD compared to 3-5 years in BOS (50). Prevalence of rCLAD is quite similar across different centers with 25-35% of CLAD patients affected (50). It is important to note that this classification is not absolute and that patients can evolve at any time during their post-transplant course from BOS to RAS or vice versa.…”
Section: Diagnosis Radiology and Pathologymentioning
confidence: 99%